HARPACTICOID COPEPODS ASSOCIATED WITH HERMIT CRABS IN THE MOLUCCAS - Humes, Arthur G. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1981)
Paguridea in the Indo-Pacific have 10 harpacticoid copepod associates: 3 Sunaristes, 3 Brianola, 1 Porcellidium, and 3 Paraidya. Four of these copepods are reported from hermit crabs in the Moluccas: Sunaristes tranteri Hamond, 1973, from Dardanus guttatus, Dardanus lagopodes, Calcinus latens, Calcinus minutus, Calcinus gaimardi, Calcinus sp., and Trizopagurus strigatus; Porcellidium brevicaudatum Thompson and A. Scott, 1903, from Dardanus guttatus, Dardanus lagopodes, Dardanus megistos, Calcinus latens, Calcinus minutus and Trizopagurus strigatus; Paraidya minor Sewell, 1940, and Paraidya major Sewell, 1940, from Dardanus guttatus, Dardanus lagopodes, and Dardanus megistos.